In vitro, in silico and in vivo study challenges the impact of bronchial thermoplasty on acute airway smooth muscle mass loss. Issue 5 (24th May 2018) - Chernyavsky, Igor L.; Russell, Richard J.; Saunders, Ruth M.; Morris, Gavin E.; Berair, Rachid; Singapuri, Amisha; Chachi, Latifa; Mansur, Adel H.; Howarth, Peter H.; Dennison, Patrick; Chaudhuri, Rekha; Bicknell, Stephen; et al.
Bronchial thermoplasty is a treatment for asthma. It is currently unclear whether its histopathological impact is sufficiently explained by the proportion of airway wall that is exposed to temperatures necessary to affect cell survival. Airway smooth muscle and bronchial epithelial cells were exposed to media (37–70°C) for 10 s to mimic thermoplasty. In silico we developed a mathematical model of airway heat distribution post-thermoplasty. In vivo we determined airway smooth muscle mass and epithelial integrity pre- and post-thermoplasty in 14 patients with severe asthma. In vitro airway smooth muscle and epithelial cell number decreased significantly following the addition of media heated to ≥65°C. In silico simulations showed a heterogeneous heat distribution that was amplified in larger airways, with <10% of the airway wall heated to >60°C in airways with an inner radius of ∼4 mm. In vivo at 6 weeks post-thermoplasty, there was an improvement in asthma control (measured via Asthma Control Questionnaire-6; mean difference 0.7, 95% CI 0.1–1.3; p=0.03), airway smooth muscle mass decreased (absolute median reduction 5%, interquartile range (IQR) 0–10; p=0.03) and epithelial integrity increased (14%, IQR 6–29; p=0.007). Neither of the latter two outcomes was related to improved asthma control. Integrated in vitro and in silico modelling suggest that the reduction in airway smooth muscle post-thermoplasty cannot be fully explained by acute heating, and nor did this reduction confer a greater improvement in asthma control. Bronchial thermoplasty treatment for asthma has unexpected possible mechanisms of action http://ow.ly/ZcuE30jsaSa